Continuous-variable quantum key distribution protocols with eight-state discrete modulation - Wahiddin, Mohamed Ridza; Becir, A; El-Orany, Faisal A. A. (World Scientific Publishing Company, 2012)
We propose a continuous variable quantum key distribution protocol based on discrete modulation of eight-state coherent states. We present a rigorous security proof against the collective attacks by taking into consideration the realistic lossy and noisy quantum channel,the imperfect detector efficiency, and the detector electronic noise. This protocol shows high tolerance against excess noise and promises to achieve over 100km distance of optical fiber.